Designing the Payout Phase of Pension Systems : Policy Issues, Constraints and Options - Rocha, Roberto; Vittas, Dimitri (2012)
This paper examines the policy issues, constraints and options facing policymakers in promoting the development of sound markets for retirement products. It discusses the various risks faced by pensioners and the risk characteristics of alternative retirement products and also reviews the risks faced by providers of retirement products and the management and regulatory challenges of dealing with these risks. The paper focuses on policies that could be adopted by developing and transitioning countries where financial and insurance markets are not well developed. It argues for promoting an adequate level of annuitization but avoiding excessive annuitization. It also argues for favoring combinations of payout options, covering different products at a particular point in time as well as different payout options over time. The paper also discusses the choice between centralized and decentralized markets and highlights the basic elements of an effective regulation of risk management.